Three Dimension Pixel Distribution Shifting Based Color Correction Method For Digital Images - Goh, Jinn Chyn (Universiti Sains Malaysia, 2017)
Color correction algorithm for a color digital image is important to reduce the influence of inhomogeneous surrounding illumination in color digital image. Commonly, existing color correction algorithms are divided into two main phases, namely color estimation and color correction. Although there are various color correction algorithms introduced by other researchers, the output images created still face some problems. Some algorithms still produce non-uniform illumination resultant image, while others methods still produce over-corrected problem in the resultant images. Thus, in this study, new color correction algorithm was developed to overcome the weaknesses of those conventional algorithms. The introduced algorithm is named as Three Dimension Pixel Shifting Color Correction (3D-PSCC). There are two variations of 3D-PSCC, which are 3D-PSCC based on RGB color channel and 3D-PSCC based on CIE*Lab color channel. Both proposed algorithms employ color correction process by shifting the pixel distribution based on the 3D three color channels planes. From the qualitative analysis results, the 3D-PSCC algorithm based on RGB color channels is able to produce better resultant images for underwater images. The bluish of the images are reduced significantly and the color of the object captured is able to be determined easily. The 3D-PSCC algorithm based on CIE*Lab color channel, on the other hand, is more suitable to correct the overexposed images. This algorithm ensures loss of information does not occur during image enhancement process. Besides that, the quantitative analysis also proves that the proposed algorithms introduced not only have the ability to correct the color of the image, but are also able to remain the brightness of the image.